PENDAMPINGAN METODE YANBU’A DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SANTRI TPQ - Agus Puspita W, Dhevin M.Q; Enti, Putri; Wahidah, Nur; Machfudin, M. (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to enhance the Qur’an reading skills of students at TPQ Puger Wetan, Puger District, Jember, through the implementation of the Yanbu’a Method. A total of 55 students actively participated in an eight-week mentoring process. The Yanbu’a Method was selected because it has been proven effective in guiding learners to read the Qur’an gradually, systematically, and in accordance with the principles of tajwīd. The mentoring activities were carried out using a Participatory Action Research (PAR) approach, which emphasizes the active involvement of the service team, instructors, and students across all stages of the program—from problem identification, planning, training, and implementation to reflection and evaluation. The results demonstrate a significant improvement in students’ fluency, accuracy of makhraj articulation, and application of tajwīd rules. In addition, the instructors became more skilled in delivering lessons using the Yanbu’a Method in a structured manner, while parental and community participation increased in supporting the learning process. Institutionally, TPQ Puger Wetan experienced strengthened management and improved instructional quality, enabling the institution to independently continue applying the method. Thus, the implementation of the Yanbu’a Method proved effective not only in improving students’ Qur’an reading competence but also in reinforcing collaboration among teachers, students, and the community in nurturing a Qur’anic-oriented generation.